2016
DOI: 10.1007/s12325-016-0454-y
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Costs Among Patients with Heart Failure: A Comparison of Costs between Matched Decedent and Survivor Cohorts

Abstract: Patients with HF who died within 1 year after an index HF encounter incurred markedly higher costs within 1 year (despite the much shorter post-index period) and PPPM costs than those who survived, with the majority of costs attributable to hospitalizations for both patient cohorts. There may be opportunities for improving outcomes in HF, considering higher use of pharmacotherapy and lower costs were seen among survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
20
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 19 publications
3
20
0
Order By: Relevance
“…In 40 (45%) studies [ 22 – 24 , 44 , 46 , 47 , 49 , 50 , 53 , 55 , 57 , 58 , 60 86 ], costs for HF-related events were (or appeared to have been) analyzed from a payer’s perspective. Three studies adopted a healthcare sector perspective [ 87 89 ]. Only two studies adopted the societal perspective [ 25 , 59 ], one study adopted the viewpoint of the patient [ 43 ], and one the hospital perspective [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 40 (45%) studies [ 22 – 24 , 44 , 46 , 47 , 49 , 50 , 53 , 55 , 57 , 58 , 60 86 ], costs for HF-related events were (or appeared to have been) analyzed from a payer’s perspective. Three studies adopted a healthcare sector perspective [ 87 89 ]. Only two studies adopted the societal perspective [ 25 , 59 ], one study adopted the viewpoint of the patient [ 43 ], and one the hospital perspective [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…The study by Obi et al [ 87 ] compared annual total medical costs between patients with HF who died to those who survived (stratified by health plan type). Authors found that patients who died incurred substantially higher costs from index to death, as compared with survivors, despite the mean post-index period being 59% shorter compared with survivors (matched cohorts).…”
Section: Resultsmentioning
confidence: 99%
“…This study required that patients had 12 months of continuous enrollment after the HFrEF index date, which meant that all included patients had survived through at least the 12-month worsening assessment period. This design contrasts with other studies that included patients who died during the period immediately following diagnosis because of the availability of mortality data, and who therefore would have incurred higher costs [ 32 , 33 ]. A retrospective claims study from a large US health plan (commercial and Medicare Advantage with Part D) showed that costs within 1 year after an HF-related encounter were markedly higher for patients who died versus those who survived during that period.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective claims study from a large US health plan (commercial and Medicare Advantage with Part D) showed that costs within 1 year after an HF-related encounter were markedly higher for patients who died versus those who survived during that period. The cost difference occurred despite the truncated post-index period for those who died, and the largest cost driver was hospitalizations [ 33 ]. Given that mortality is associated with increased cost, the present study likely underestimates costs during the worsening assessment period by including only patients with 12 months continuous enrollment after HFrEF diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…9 More recently, there has been a heightened awareness in frequent users of the ER for ADHF, because of both the system costs associated with frequent use of acute services and the associated mortality burden shortly after discharge. 10,11 Previous research has examined ways to risk stratify patients with HF presenting to the ER, particularly to understand the risk of repeat ER visits, hospitalization, or death. 12 One aspect of this patient population that has not been examined is the subset of patients with HF who present to the ER multiple times within a short time frame after discharge.…”
mentioning
confidence: 99%